Hubungan Pola Konsumsi Sayur dan Buah Dengan Kejadian Obesitas Pada Remaja di SMA Negeri 2 Negara - Wirawan, I Kadek Andi; Puryana,STP., MP., I Gusti Putu Sudita; Agustini,SKM., M.Si., Ni Putu (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2025)
Obesity is excess body weight,measured by a body Mass Index (BMI) of more than 30 kg/,wich is a goal problem,affecting 2 billion people,and is expected to affect 1 in 7 men and 1 in women by 20230.This study aims to determine the relationship between vegetable and fruit consumplition pattems and the incidence of obesity in adolescents at SMA Negeri 2 Negara.This type of research is observational with a cross-sectional design,conducted in April – May 2024 with a population of 733 people and a sample of 88 people using proportional random sampling.Date were collection throught questionnaires,SQ-FFW,and BMI/U measurements.The results of the analysis showed that most samples had vegetable and fruit consumption patterns showing that most samples (58%) with good patterns,27 samples (30,7%) sufficient,and 10 samples (11,4%) lacking.There were 15 samples (17%) who were obese and 73 samples (83%) were not obese.Chi-Square test shows there is a relationship between vegetable and fruit consumption patens and obesity incidence (p-value = 0,000).The suggestion that can be conveyed is that adolescents should apply the principle of balanced nutrition by routinely consuming vegetables and fruits and schools are expected to work together with health workers to provide counseling and education regarding the impotance of vegetable and fruit consumption.